Samuel P. Church, The Revised Ordinances of the City of Quincy, Illinois 47 (1841) - (:unkn) unknown (My University, 1841)
§ 5: Prohibited the discharge of any cannon, musket, rifle, fowling piece, or other fire arms, air-gun, cracker, rocket, torpedo, squib, or other fire works within city limits. Violators fined not less than one, nor more than three dollars for each offense.
Keywords: DISCHARGE